THE INFLUENCE OF SERVICE QUALITY AND PROMOTIONS ON PURCHASING DECISIONS AT GRAND BOWLING SERPONG BRANCH - Ahyani Ahyani; Suharni Rahayu; Hafis Laksmana Nuraldy; Rr. Ayu Metarini (International Journal Multidisciplinary Science, 2024)
This research explores the impact of service quality and promotions on consumer purchasing decisions at Grand Bowling, both partially and simultaneously. The research method used is a quantitative associative approach. The sample was selected using a saturated sampling method using the Slovin formula, which resulted in a sample of 99 respondents. The data collection tool used was a questionnaire, while data analysis was carried out through simple and multiple regression analysis. The research results show that service quality and promotions positively and significantly influence purchasing decisions. This is proven through a multiple linear regression model, which produces the equation Y = 4.488 + 0.535X1 + 0.757X2. Overall, service quality and promotion simultaneously have a positive and significant effect on purchasing decisions, as shown by the results of the F test with a significance of 0.000 < 0.050. These findings confirm that the quality of service and promotions influences consumer purchasing decisions at Grand Bowling.